1990
DOI: 10.1136/bmj.301.6747.321
|View full text |Cite
|
Sign up to set email alerts
|

Activities of aminotransferases after treatment with streptokinase for acute myocardial infarction.

Abstract: been reported cytologically as non-neoplastic the cytological specimens were reviewed. In one case from the first year of the study a retrospective cytological diagnosis of papillary carcinoma was made, but in all other cases there were no cytological features suggesting neoplasia, although in two cases the specimens would now be classed as unsatisfactory.Aspiration cytology is an adjunct to the management of thyroid swellings but is not a definitive diagnostic test and, in particular, negative results do not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Sallen et al [14] and Freimark et al [15] reported a cytolytic hepatic pattern without changes in bilirubin blood levels, whereas our patient had high blood levels of total and direct bilirubin. Maclennan et aL [3] similarly described that treatment of acute myocardial infarction with streptokinase could lead to a rise in the levels of alanine aminotransferase, aspartate aminotransferase, bilirubin and gammaglutamyl transferase.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…Sallen et al [14] and Freimark et al [15] reported a cytolytic hepatic pattern without changes in bilirubin blood levels, whereas our patient had high blood levels of total and direct bilirubin. Maclennan et aL [3] similarly described that treatment of acute myocardial infarction with streptokinase could lead to a rise in the levels of alanine aminotransferase, aspartate aminotransferase, bilirubin and gammaglutamyl transferase.…”
Section: Case Reportmentioning
confidence: 99%
“…In fact, they have been shown to be mediated by circulating immunoglobulins [2]. Other secondary effects of this agent are hyperthermia, hypotension, elevated levels of hepatic enzymes [3] and haemorrhagic complications.…”
Section: Introductionmentioning
confidence: 99%